Capital Structure and Performance of Non-Financial Firms in Sub-Sahara Africa - Evbayiro-Osagie, Esther Ikavbo; Enadeghe, Iyobo Best (International Journal of Finance Research, 2022)
The study examines the impact of capital structure on return-on-assets (ROA) performance of non-financial firms in Sub-Sahara Africa for a period of nine (9) years (2012-2020). A total of forty (40) non-financial firms were studied using their capital structure variables of long term debt to equity (LTDQ), total debt (TD), total debt to equity (TDQ), and total debt to total assets (TDTA) as well as their ROA performance. The panel data analysis technique was employed. It was found that LTDQ, TD and TDQ have positive impact on ROA performance; while TDTA has a negative impact on ROA performance, and all variables were significant at 1 percent level. The study recommends that, since long term debt to equity strongly explain corporate performance in the Sub-Saharan African Countries, management should sustain their current policies and should also be very sensitive in determining the appropriate amount of long term debt that ought to be included in their capital structure build up.